1981
DOI: 10.21273/jashs.106.3.385
|View full text |Cite
|
Sign up to set email alerts
|

Germination Studies of Clay-coated Sweet Pepper Seeds1

Abstract: Seed germination of sweet pepper (Capsicum annuum L.) is inhibited after the seed is coated. The inhibitory effect of pellet-coating of ‘Early Calwonder’ pepper seed was caused by the physical properties of the coating materials. Clay coating limited part of the oxygen (O2) from reaching the germinating seed and provided a mechanical barrier to protrusion of the radicle. Clay-coated pepper seed germinated satisfactorily on filter paper in a high O2 environment or with minimum moisture on agar. Pellet coating f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
3

Year Published

1982
1982
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 1 publication
0
9
0
3
Order By: Relevance
“…Thus the intact coating may have restricted gas movement between the seed and its environment. Sachs et al (15) observed a slow germination rate of clay-coated pepper seeds in air, but noted an increase after transferring the seeds to an oxygen-rich environment. They concluded that the slow germination in air was due to the seed coating restricting oxygen diffusion between the seed and its environment.…”
Section: Discussionmentioning
confidence: 99%
“…Thus the intact coating may have restricted gas movement between the seed and its environment. Sachs et al (15) observed a slow germination rate of clay-coated pepper seeds in air, but noted an increase after transferring the seeds to an oxygen-rich environment. They concluded that the slow germination in air was due to the seed coating restricting oxygen diffusion between the seed and its environment.…”
Section: Discussionmentioning
confidence: 99%
“…The procedures used in experiments where high 0 2 environ ment was tested were similar to those previously described (11). To increase 0 2 levels in the microenvironment of the germinating seed, barium peroxide (B a02) or sodium perborate (NaB03) were incorporated into the outer layers of the pellets during the sand-coating procedure.…”
Section: Methodsmentioning
confidence: 99%
“…Samples of sand-and clay-coated seeds were examined with a Hitachi S 450 scanning electron microscope. The preparation and viewing of specimens were the same as previously described (11). Osmotic values for the germination medium (the seed and coating materials leachate) were recorded using a vapor pressure osmometer (Wescon, Inc. Model 5130B).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased germination and germination rate of several species has been achieved by increasing the 0 2 concentration (4,6). Sachs et al (11) found that clay-coated pepper seeds germinated faster in an environment of 100% 0 2. They suggested that the clay coating limited 0 2 supply to the embryo and thus inhibited germination at 0 2 concentrations of 21%.…”
mentioning
confidence: 99%